(3GdefJbi ef GdLRA GdYGTQ ef JGQjN GdESdGes - (3CMeO Hf eMeO Hf Ydj GdMUcaj, GHf GdedG ,J (B1003 (3g` s ((3GHf bGVi TgHI(B- (3HGdebGQfI s)
(3ChdgG (B:s
(3GdWHbI GdSGOSI hGdYTQhf s
(3BNQgG (B:s
(3BNQ GdefJbi ef GdLRA GdYGTQ ef JGQjN GdESdGe s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QGLY ajde Qbe (B181 (3h(B183 (3chjJs
(3YdjgG eWGdYI hJedc s
(3gPg GdLRA JhGQjN ef SfI (B250 (3g Edi BNQ (B300 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs